The Effectiveness of the Use of Boss Funds and School Financial Management through RKAS in Improving the Quality of Education Services (Case Study at Uptd Sd Negeri No. 078459 Soi'iwa) - Frenjert, Hadiedwar; Waruwu, Arman Lius Waruwu Lius; Gulo, Karyaksi Damai; Rakhmansah, Yousep Rakhmansah (Journal of English Language and Education, 2025)
This study aims to analyze the effectiveness of the use of School Operational Assistance (BOS) funds and school financial management through the School Activity and Budget Plan (RKAS) in improving the quality of educational services. A case study was conducted at UPTD SD Negeri No. 078459 Soi’iwa based on the 2025 RKAS, in-depth interviews, and observations. The research method used is descriptive qualitative with data triangulation. The results show that most BOS funds are allocated to Infrastructure Standards (34.03%), Management Standards (45.88%), and learning support activities. School financial management has met the principles of transparency and accountability, although there are still limitations in funding learning innovations. The RKAS has proven to be a strategic instrument for budget planning and control to achieve educational goals.